PELATIHAN DAN PENDAMPINGAN DESAIN PEMBELAJARAN DIGITAL BERBASIS GOOGLE APPS SCRIPT DAN LUMI EDUCATION - Moch. Fauzi; Mohammad Ridho’i; Gati Ayu Likasari; Ana Rokhmawati; Naily Rizqi Amaliyah (Dharma: Jurnal Pengabdian Masyarakat, 2026)
The rapid development of digital technology requires teachers to possess competencies in designing innovative and interactive digital learning. However, many educators still face challenges in developing digital learning media that are adaptive, interactive, and easily integrated with existing learning platforms. Therefore, this community service program aims to improve teachers’ competencies in designing digital learning through training and mentoring using Google Apps Script and Lumi Education. The activities were conducted through several stages, including needs analysis, training workshops, hands-on practice, mentoring sessions, and evaluation. During the training, participants were introduced to the fundamentals of digital learning design, the use of Google Apps Script to automate and integrate learning resources within the Google ecosystem, and the development of interactive learning content using Lumi Education based on the H5P framework. The mentoring process allowed participants to directly design and develop digital learning media relevant to their teaching subjects. The results of the program indicate that participants showed increased understanding and skills in developing interactive digital learning media. Teachers were able to create simple automated learning tools, interactive quizzes, and multimedia-based learning materials that support student engagement. In addition, participants demonstrated positive responses toward the implementation of the training and mentoring activities, as these tools were considered practical, accessible, and applicable in classroom practice. Thus, this community service activity contributes to strengthening teachers’ digital pedagogical competencies and supports the implementation of technology-integrated learning in the digital era.